Deep Recurrent Neural Networks Based Obstacle Avoidance Control for Redundant Manipulators - Xu, Zhihao; Zhou, Xuefeng; Li, Shuai (Frontiers in Neurorobotics, 2019)
Obstacle avoidance is an important subject in the control of robot manipulators, but is remains challenging for robots with redundant degrees of freedom, especially when there exist complex physical constraints. In this paper, we propose a novel controller based on deep recurrent neural networks. By abstracting robots and obstacles into critical point sets respectively, the distance between the robot and obstacles can be described in a simpler way, then the obstacle avoidance strategy is established in form of inequality constraints by general class-K functions. Using minimal-velocity-norm (MVN) scheme, the control problem is formulated as a quadratic-programming case under multiple constraints. Then a deep recurrent neural network considering system models is established to solve the QP problem online. Theoretical conduction and numerical simulation show that the controller is capable of avoiding static or dynamic obstacles, while tracking the predefined trajectories under physical constraints.